Virtual team effectiveness: the role of trust and team learning - Zhu, Qili (2020)
With the development of global information electronation, the fiercely competitive environment makes the business model of enterprises more and more complex, and the virtual team is accepted generally. Virtual teams across cultures, regions and organizations can solve the problem of difficult assistance caused by space and time. This new team model has become a significant direction of theoretical study and practice in recent years. In the virtual team, this study has three variables: trust, team learning and team effectiveness. The purpose is to study the role of trust and team learning on the effectiveness of virtual teams. Also, examine the mediating role of team learning in the relationship between trust and team effectiveness. In this model, team effectiveness is measured from three dimensions, including task performance, satisfaction and development ability. With the virtual team members as the research object, 348 questionnaires were used to collect data. Through correlation analysis, regression analysis, mediation verification, variance analysis and other research methods, the hypotheses of the research model are verified and tested. The data shows that trust has different degrees of significant impact on the three dimensions of team effectiveness, and trust can also affect the effectiveness of virtual teams through the mediation of team learning.